681 Postoperative Muscle Relaxant Use Associated With Increased Risk of Delirium Following Lumbar Spinal Fusion. (April 2023) - Piscopo, Anthony; Perez, Eli; Woodroffe, Royce
Abstract : INTRODUCTION: Muscle relaxants including cyclobenzaprine and baclofen are frequently utilized in pain management following spine surgery as part of enhanced recovery after surgery (ERAS) protocols. These medications are associated with anticholinergic and central nervous system side effects and are used with caution in outpatient treatment for those at high-risk of delirium, especially the elderly. Literature investigating their association with delirium in the postoperative setting has not been described. METHODS: Patients over age 65 undergoing elective posterior lumbar fusion between 2017 and 2021 at the senior author's institution were retrospectively reviewed. Variables collected included patient demographics as well as whether subjects received postoperative administration of baclofen and/or cyclobenzaprine on postoperative day 1 as part of a multimodal analgesia regimen. Doubly-robust inverse probability weighting (IPW) with cox-regression was used to evaluate the incidence of postoperative delirium between groups. RESULTS: Five-hundred and thirty-one patients were included in the analysis. Incidence of delirium in those who received postoperative muscle relaxants was 17.6% (44/250) compared to 11.4% (32/281) in the control group who did not (p = 0.001). Doubly-robust IPW analysis found patients who received muscle relaxants were at a 2.07 (95% CI: 1.18-3.63) times increased risk of delirium compared to controls (p = 0.015). Postoperative time to delirium onset was similar between groups (3.0 vs 3.1 days; p = 0.916) while the average duration of delirium was significantly longer in those who received postoperative muscle relaxants (2.5 vs 1.6 days; p = 0.008). CONCLUSIONS: Postoperative muscle relaxant use was associated with a higher risk of delirium in elderly adults following lumbar spinal fusion. Although muscle relaxants may assist with postoperative pain control as part of ERAS protocols while minimizing opioid administration, their side effect profile should be considered in patients at high risk of postoperative delirium.